Dietary patterns and dietary recommendations achievement from Latin American college students during the COVID-19 pandemic lockdown - Murillo, Ana Gabriela (2022)
Fil: Murillo, Ana Gabriela. University of Costa Rica. School of Medicine. Department of Biochemistry; Costa Rica